Flag Desecration Statutes: History and Analysis - Albert M. Rosenblatt (Washington University Law Quarterly, 1972)
The Article describes a variety of cases dealing with different ways that the American flag has been “desecrated,” including burning, flag-wearing, and its use in advertising. It also looks at some of the rationales by which those accused of desecrating the flag have used to justify their actions.
Keywords: Freedom of speech